2012
DOI: 10.1111/j.1467-971x.2012.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Dutch‐accented English

Abstract: This paper reports on a study into the reactions of 'native' speakers of British English to Dutch-English pronunciations in the onset of a telephone sales talk. In an experiment 144 highly educated British professionals who were either familiar or not familiar with Dutch-accented English responded to a slight Dutch English accent, a moderate Dutch English accent or a 'Standard British English accent' (BrE). These accents were rated on the personality traits status and affect, on their intelligibility (orthogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 25 publications
(48 reference statements)
8
63
5
Order By: Relevance
“…People with a moderate Dutch accent in English were accorded less status than people with a slight Dutch accent or a native English (RP) accent (Nejjari et al. ). The alternative view that Dutch people should not adhere to Inner Circle norms, but stick to their own variety of English, ‘Dunglish,’ is also propagated, but far less frequently.…”
Section: The Spread Of English In the Netherlandsmentioning
confidence: 99%
“…People with a moderate Dutch accent in English were accorded less status than people with a slight Dutch accent or a native English (RP) accent (Nejjari et al. ). The alternative view that Dutch people should not adhere to Inner Circle norms, but stick to their own variety of English, ‘Dunglish,’ is also propagated, but far less frequently.…”
Section: The Spread Of English In the Netherlandsmentioning
confidence: 99%
“…One example of such research is native listeners' evaluation of non-native pronunciation. Research has shown that native speakers evaluate speakers with a non-native pronunciation as less competent than speakers with a native pronunciation (e.g., Nejjari, Gerritsen, Van der Haagen, & Korzilius, 2012). Another example is native-reader perception of textual and visual choices that non-natives make.…”
Section: Non-nativeness In Communicationmentioning
confidence: 96%
“…While results on social attractiveness qualities vary, nonnative speakers are nearly always evaluated lower on status traits than are native speakers, both by native listeners (Ball, 1983;Eisenchlas & Tsurutani, 2011;Nejjari et al, 2012;Ryan & Bulik, 1982;Ryan et al, 1977) and by nonnative listeners (Chiba et al, 1995;Dalton-Puffer et al, 1997;He & Zhang, 2010;McKenzie, 2008McKenzie, , 2010Xu et al, 2010;Yook & Lindemann, 2013).…”
Section: Bias Against Nonnative Speakersmentioning
confidence: 99%